2020
DOI: 10.1007/s10198-020-01175-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a non-pharmacological treatment vs. “care as usual” in day care centers for community-dwelling older people with cognitive impairment: results from the German randomized controlled DeTaMAKS-trial

Abstract: Background Cognitive impairment in older adults causes a high economic and societal burden. This study assesses the costeffectiveness of the multicomponent, non-pharmacological MAKS treatment vs. "care as usual" in German day care centers (DCCs) for community-dwelling people with mild cognitive impairment (MCI) or mild to moderate dementia over 6 months. Methods The analysis was conducted from the societal perspective alongside the cluster-randomized controlled, multicenter, prospective DeTaMAKS-trial with wai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 75 publications
(137 reference statements)
0
9
0
1
Order By: Relevance
“…Another community-based study ( 4 ) found that 30% of Chinese older adults aged over 80 years suffered from cognitive impairment. Cognitive impairment could result in negative consequences, including reduced quality of life (QOL), impaired functional outcomes and increased health care burden ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another community-based study ( 4 ) found that 30% of Chinese older adults aged over 80 years suffered from cognitive impairment. Cognitive impairment could result in negative consequences, including reduced quality of life (QOL), impaired functional outcomes and increased health care burden ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The administrative data of social and health care service use and the costs of the intervention will be utilized in examining the cost-effectiveness of the intervention [ 34 ]. Costs of the day activity service will be retrieved from the service providers.…”
Section: Methodsmentioning
confidence: 99%
“…Example of Item 12: Measurement of outcomes 101,102 "We conducted a cost-effectiveness analysis (CEA) alongside the cluster-randomized, controlled, multicenter, prospective DeTaMAKS-trial ..Further details on the recruitment strategy of DCCs and the eligibility criteria of DCCs and participants are described in detail elsewhere.The trial's registration number is ISRCTN16412551. The effect of MAKS on cognitive abilities was operationalized by the Mini Example of Item 13: Valuation of outcomes 116,117 "Under this approach, the health outcome in conventional costutility analyses, namely QALY, was monetised using individual WTP for an additional QALY gained.…”
Section: Explanation Analyses Based On Preference-based Outcomementioning
confidence: 99%